Profesioanalism of Islamic Religion Teacher to Increase Students’ Learning Quality in State Senior High School 17 Surabaya - Wafir Hasanudin (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2018)
This study aims to reveal the Professionalism of Islamic Religious Education teacher in State Senior High School 17 Surabaya in improving the students’ learning quality. As well as improving the students’ learning quality in State Senior High School 17 Surabaya. The method used in this research is analytical descriptive research that is a research that aims to give a picture of reality on object that is studied objectively. The source of the research data obtained from observation, interview, questionnaire and documentation. This research took place from December 15, 2017 to February 15, 2018. Research proved that the professionalism of Islamic Religious Education teacher in State Senior High School 17 Surabaya is good enough. Professional teachers are teachers who can be mature, able to control themselves, not easily carried away emotions. Be objective, teachers who have academic qualifications in accordance with their field of Bachelor of Islamic Religious Education, have four competencies (pedagogic competence, knowledge, personality and social competence). So that, students’ learning quality will increase and having quality as expected. Keywords: Islamic Religious Education Teachers, Professionalism, Quality of Learning